Assessment of Anti-Mullerian Hormone (AMH) levels in a pilot cohort of peripubertal females: Correlation with sex maturity rating (SMR) - F.F. AbdelHafez; Y. Tang; M.H. Hassan; T.H. Saleem (Middle East Fertility Society Journal, 2018)
Objective: Anti-Müllerian Hormone (AMH) is a quantitative marker for ovarian reserve found to be independent of the menstrual cycle. The objective of this study was to determine whether serum AMH levels correlate with sex maturity rating (SMR) in a group of peripubertal elementary school girls. Study design: This cohort study was conducted in a tertiary care facility. Baseline blood sampling was obtained in 71 peripubertal healthy elementary school girls from Upper Egypt. AMH was measured using commercially available kit (DSL Inc., Webster, TX, USA). SMR was determined clinically through observations of pubic hair and breast development rated from 1 (preadolescent) to 5 (mature adult female).A bivariate analysis was conducted between age, weight, SMR, and the AMH level. Data was stratified for further analysis by SMR, and SMR 3 and 4 were combined to ensure suitable sample size. Statistical analysis was done using R software version 3.2.2 (R Foundation for Statistical Computing, Vienna, Austria). Results: Seventy-one observations were analyzed with a mean age of 9.31 ± 1.80 years. Mean weight was 28.87 ± 7.45 kg, and the mean AMH level was 2.05 ± 0.52 ng/mL. SMR observations included 15 with SMR of 1 (21%), 26 with SMR of 2 (37%), 26 with SMR of 3 (37%), and 4 with SMR of 4 (6%). There were no significant associations between age, weight, SMR and AMH level. Upon stratifying the analysis by SMR, a significant correlation was found between age and AMH within the SMR of 3 and 4 grouping (rho = −0.4194, p = 0.02106). When considering all variables for regression it was found that the model that best fit the data was comprised of only an intercept term. Age, weight, and SMR were not included in the final regression model. Conclusion: The correlation of AMH with an advanced stage of maturation (SMR 3&4) may reflect modest late pubertal AMH peaks in this population of females. The proportionate association of AMH with breast development, reflective of the gonadotropins and steroidogenic functions, supports its role as a marker of ovarian function in young females. Keywords: Anti-Mullerian Hormone (AMH), Peripubertal females, Sexual maturity rating, Growth and development